(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the phenomenon of aphasia from both linguistic and neurological perspectives. Aphasia is a complex psychoneurological condition characterized by speech impairment resulting from damage to specific areas of the brain. The main aim of the research is to identify and analyze the causes of aphasia, its main types—particularly Broca’s and Wernicke’s aphasia—as well as various forms of speech disorders based on the classification proposed by A.R. Luria. The article provides a detailed overview of the contributing factors (such as stroke, brain injuries, etc.), symptoms of aphasia, the specific features of each type, and the possibilities for treatment and rehabilitation. It also examines linguistic approaches to working with patients affected by aphasia, along with theoretical and practical methods of speech recovery. The research findings indicate that each type of aphasia has distinct characteristics and requires an individualized approach. In conclusion, the article presents an in-depth analysis of the phenomenon of aphasia and justifies the relevance of scientific studies conducted at the intersection of linguistics and neurology